Absorption studies of methylene blue on inverse opal titania - Chen, Qijia. (2009)
Titanium dioxide, TiO2, is a widely used material used in photocatalytic applications. Due to its importance in relation to environmental uses, studies have been carried out with regards to synthesis and methods for wastewater treatment. This project investigates the adsorption characteristics and mechanisms of different forms of TiO2, namely, commercially available Degussa P25, Powder and 3DOM (Inverse Opal Macroporous). Precipitation method and sol-gel methods were adopted to synthesize TiO2 Powder and 3DOM respectively. Variables investigated include time, temperature and concentration of methylene blue (MB). It was observed that adsorbents undergo physical adsorption with MB (adsorbate) and among all adsorbents investigated; 3DOM has the most efficient adsorption capacity to be utilized in photocatalytic applications, as a monolayer of adsorbent is desired to activate the active sites of TiO2 upon exposure to UV light. In addition, the interconnected network pore structure of 3DOM observed in SEI suggested that a larger surface area implies a higher efficiency, as saturation of MB (constant line of relative absorbance) was observed with a shorter time period. Powder and P25, on the other, being bulk in nature suggests adsorption mechanism followed by absorption of MB. Adsorption is an exothermic process and the kinetics reaction was suggested to be dependent on the initial concentration of MB, fitting 2nd order kinetics model for both P25 and powder. It was observed that different adsorption mechanisms; 2nd order and intra-particle diffusion, exist for 3DOM. Degradation of MB was observed at 40°C, and the effect of adsorption is inconclusive when investigated with a concentration below 6ppm. Further investigation can be performed with characterization tools such as XRD and BET to observe the effect and the number of active sites that influences the adsorption capacity of the adsorbents. Different sizes of 3DOM structures may be investigated to compare the viability and adsorption capability of various sized structures.